21st Century Learning Based on 4C Skills (Critical Thinking, Communication, Collaboration and Creativity and Innovation) Against Literacy Culture in Elementary Schools - Yana Erlita Hakim; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
21st century learning is learning that prepares the 21st century generation with three main subjects in learning, namely: 1) Learning and Innovation Skills, 2) Information, Media, and Technology, and 2) Life and Career Skills. This study aims to conduct a literature review related to 21st century learning based on 4C skills (Critical Thinking, Communication, Collaboration and Creativity and Innovation) on literacy culture in elementary schools. The method used in this research is SLR (Systematic Literature Review). Data collection is done by documenting and reviewing all articles related to 4C Skills published in the period 2018-2022. The articles used in this study were 20 journal articles. Based on this research, it was found that the 4C skills (Critical Thinking, Communication, Collaboration and Creativity and Innovation) 1) had a positive influence on increasing students' HOTS abilities, 2) developing one or several potentials that existed in students, 3) increasing interest and student learning outcomes, 4) improve literacy culture in the school environment, 5) improve literacy in various subjects, 6) improve understanding and mastery of subject matter concepts, and 7) improve students' awareness of sustainability skills effectively. So that 4C skills can be used in elementary schools, especially in terms of literacy culture.